Analisis Strategi Kesiapan Pemerintah Desa dalam Pembentukan Badan Usaha Milik Desa di Kabupaten Sumenep - Mawardi, Moh Maqbul; Majid, Ach Nurholis; Dzulkarnain, Iskandar (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
This research has three focuses. First is reporting the readiness strategies to establish Village-owned enterprises (BUMDes) in the Sumenep regency. The second is representing supporting and inhibition factors in the formation of the BUMDes in the Sumenep regency. The third is defining the typology of the village in responding to the BUMDes program in the Sumenep Regency area. This research is a qualitative-descriptive method by applying SWOT analysis conducted in 2020 from October to December. The data is collected by using observation, interviews, documentation, and a literature study. Based on the data obtained from this research, first, Based on the SWOT analysis data in Quadrant SO (strength - opportunity) Level, some strategies can be used. Those are by making local regulations of the formation of BUMDes, increasing the understanding of village heads towards the technical establishment of BUMDes, which is not only limited to theoretical knowledge, improve the role of DPMD in responding to proposals for the establishment of BUMDes. There needs to be a technical introduction about village potential that can be explored using the ABCD (Asset-Based Community Development) method. Second, there are some factors to support the establishment and development of BUMDes in the Sumenep area. One of which is to provide the head of villages with the knowledge and urgency of BUMDes establishment. As every town are highly potential and meet the requirements. However, there is no specific direction and method in establishing BUMDes that has become an obstacle in determining the potential and managing the BUMDes. Third, BUMDes in Sumenep consists of three typologies. Those are BUMDes that have not been established, which only succeeded in the proposal preparation stage. Then, The established BUMDes with less income. The last is the well-developed BUMDes that have been contributed to the villages' income.